Waqf Development for Responsible Consumption and Production - Rusydiana, Aam Slamet; Sukmana, Raditya; Laila, Nisful; Ali, M. Mahbubi (SMART Insight, 2023)
The discussion on responsible consumption and production is summarized in the twelfth SDGs goal. On the other hand, waqf is an instrument of Islamic social funds that has a sustainable nature and has the relevance of waqf to the SDGs, so it has the potential to be developed in its role in responsible consumption and production and its impacts. This study seeks to see the waqf development model that is relevant to the goals of the SDGs by determining the priority of the waqf model that can be applied in Indonesia which is in line with the objectives of SDG-12. The results of the study indicate that the Waqf & ZIS model is the right model to support the achievement of the twelfth goal of the SDGs, namely responsible consumption and production. This study also proposes a waqf-based waste management system that is suitable for this purpose.